PENGARUH PENGIMBASAN ASAM SALISILAT TERHADAP TANAMAN SINGKONG (Manihot esculenta Crantz) SEBAGAI AGEN KETAHANAN JAMUR Fusarium oxysporum - Yuniar, Lutfiah (UNIVERSITAS PGRI MADIUN, 2023)
Cassava is an important food crop commodity in Indonesia after rice, corn, soybeans, peanuts and green beans. When planting cassava, there are disease attacks caused by fungi, one of which is the Fusarium oxysporum fungus. One alternative method that can be done is by inducing salicylic acid in cassava (Manihot esculenta Crantz) to make it resistant to fungal attacks. This research aims to determine the resistance of cassava plants to the Fusarium oxysporum fungus. The method that will be used is a Completely Randomized Design (RAL) with 5 levels of salicylic acid concentration, namely 0 ppm, 80 ppm, 100 ppm, 120 ppm and 140 ppm with 5 replications. Observation data consists of number of leaves, number of shoots, and root length. Analyzed using analysis of variance (ANOVA) at a real level of 5% and further tested with the BNT test (Least Significant Difference) at a real level of 5%. The effective concentration for cassava plants infected with the fungus Fusarium oxysporum is a concentration of 100 ppm.Keywords: Cassava, Salicylic Acid, Fusarium oxysporum.